(untitled) (Medical Forum Monthly, 2024)
Objectives: To observe the frequency of non-firearm fatalities in interior of Sindh. Study Design: Observational / descriptive study. Place and Duration of Study: This study was carried out in the Mortuary of Liaquat University Hospital Hyderabad (LUH) from1st January, 2015 to 31st December, 2015. Materials and Methods: Fatality records were obtained from mortuary of (LUH) Hyderabad, which comprises of police inquest reports and postmortem reports. During study period 217 cases of Medico legal deaths were brought for postmortem examination in the mortuary of LUH. All cases were sorted according to age, sex and cause of medico legal / unnatural deaths and data was analyzed. Results: The most common type of unnatural death found in every age group was homicide. Among 155 homicidal deaths, road traffic accidents seen in 57 cases (36.77%) as the major cause of death mostly accidental but sometimes may be homicidal. Next cause is sharp weapons which engulf lives of 30 (19.35%) humans. Only 02 (1.29%) cases of suicide were brought to medico legal section. In 05(3.22%) cases cause of death remains undetermined. Out of total 155 cases, 118 were males (76.12%) and females were 37(23.87%). The age group most commonly involved was of 21-40years; next group with majority is between ages of 41-60 years while death in 01-20 years of age is equal to deaths in age group of 61-80 years. Conclusion: Our study concludes that among the homicidal deaths non firearm fatalities are predominately due to road traffic accidents followed by sharp weapons.